Analisis Pengaruh NPF dan FDR terhadap Profitabilitas dengan CAR Sebagai Variabel Intervening - Raihani Fauziah; Muhamad Umar Mai; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The background of this research is due to unstable fluctuations in ROA, which shows that Islamic banks have not been able to maintain their stability, so research on profitability is needed. This study aims to determine the effect of NPF, FDR, on profitability with CAR as the Intervening variable for the case study of Islamic Commercial Banks for the period 2011-2020. The data collection method is by accessing data on financial ratios of each bank through the OJK website with purposive sampling as the sample used. The research method is quantitative research and uses WarpPLS 8.0 software. The findings of this study are to contribute to BUS regarding the factors that affect the profitability of Islamic Commercial Banks. From this study, it was found that the NPF and FDR variables had a significant negative effect on profitability, while the CAR had a significant positive effect. The NPF variable has a significant negative effect on CAR and the FDR variable has a significant positive effect. Based on the results of the path analysis test, CAR is able to mediate the effect of NPF on profitability, while for FDR, CAR is not able to mediate the relationship of FDR to profitability.